EVALUASI PERATURAN WALIKOTA SURABAYA NOMOR 19 TAHUN 2022 TENTANG KEBIJAKAN RUMAH PADAT KARYA DI GUBENG SURABAYA - Sugiharto, Mulus; Azizah, Ismi (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2024)
Poverty is a multidimensional problem related to the inability to access economic, sociocultural, political, and participation in society. Poverty is also one of the problems faced by people in urban areas, until now the problem of poverty has not been resolved. The government has tried to overcome this problem through the Urban Poverty Reduction Program (PPKP), with one of its programs through the Urban Labor Intensive Program (PKP). This research uses qualitative research with a descriptive approach, using public policy evaluation dimension criteria to evaluate the implementation of the Viaduct by the Gubeng Labor-Intensive House Program according to William Dunn. This study aims to evaluate and determine the supporting and inhibiting factors for implementing the Labor Intensive program through Viaducy by Gubeng in Gubeng District, Surabaya City. The efficiency of the evaluation of the Viaduct by Gubeng Labor-Intensive House Program cannot be said to be efficient because the Surabaya City Government's efforts to finance the Viaduct by Gubeng until it can stand as it is now have not completely alleviated poverty in Gubeng District. Suggestions can be given that can later improve or improve the activities of the Viaduct by Gubeng Labor Intensive Policy Program: 1. It is necessary to implement a work package program whose training is more specific to Labor-Intensive programs such as one of them is Viaduct by Gubeng 2. The Surabaya City Government must focus more on the talents and interests of the people of Gubeng District.